Managing Governmental Public Relations in Russia: Evidences from St. Petersburg - Bykov, Il'ia A.; Pobedinskiy, Igor M.; Achkasova, Vera A.; Kuzmin, Aleksey E. (International Review of Management and Marketing, 2016)
The paper deals with the problems of media relations management in governmental organizations in Russia. Governmental Public Relations (PR) became one of the fastest developing areas of the PR-industry in contemporary Russia. The study uses expert survey method in order to unveil true mechanisms of governmental public relations in Russia. The authors of the study have interviewed sixteen high-ranking experts. The findings of the study shows that governmental PR in Russia are very well developed in the executive branch of power while it is close to zero in the jurisdictional branch and very weak in the legislative branch of power. Another important result deals with the significant role of governmental financial support to the mass media, which influences governmental PR in the way of corruption and miscommunication with the public. Keywords: PR, governmental PR, media relations, political communication JEL Classifications: D73, H83